MODEL BISNIS MEDIA ONLINE NYTIMES.COM - AB Sarca Putera (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2022)
Today's most fundamental problem with online media is finding a suitable business model to adapt to the digital world. This study aims to determine how nytimes.com applies the implementation of the business model. Using a qualitative approach, this research applies the case study method with literature studies, literature analysis, and audio-visual material as the data collection techniques. In the first stage, disruptive innovation theory is used to read the pattern of online media development. The next stage, the nytimes.com business model is analyzed using a four-element business model: value proposition, resources, processes, and profit formula. This study found that nytimes.com embodies the value proposition in the practice of service journalism with the orientation of providing services and guidance for readers. Meanwhile, the collaboration between the quality of newspaper journalists and the digital team in the Interactive News Team, Beta Team, and Express Team units supports nytimes.com's resources. Furthermore, in the component process, nytimes.com prioritizes collaboration between departments. Finally, in formulating the profit formula, nytimes.com adheres to three revenue models: subscription, advertising, and transactional